Thermo-Hydraulic Performance Evaluation, Field Synergy, and Entransy Dissipation Analysis for Hexagon-Like and Circular-Like Pin Finned Tube Bundles. Issue 13 (27th August 2018) - Tian, En; He, Ya-Ling; Tao, Wen-Quan
ABSTRACT: In this paper, a comprehensive thermo-hydraulic performance evaluation for air flow across the hexagon-like and circular-like staggered pin finned tube bundle heat transfer surfaces has been numerically carried out by adopting the performance evaluation plot of enhanced heat transfer techniques oriented for energy-saving. In addition, the simulation results have also been analyzed from the viewpoints of field synergy principle and entransy dissipation extreme principle. The results indicate that the heat transfers are all enhanced based on identical pressure drop for the hexagon-like and circular-like pin finned tube bundles within the inlet velocity range from 1 m/s to 10 m/s studied. Moreover, the circular-like pin finned tube bundle offers the lowest friction factor increase ratio for the same Nusselt number increase ratio. Furthermore, the synergy between velocity and fluid temperature gradient has been proved again, having inherent consistency with the dissipation of entransy.